Effects of COVID-19 lockdown and a subsequent retraining period on elite athletes` workload, performance, and autonomic responses: A case series - Valenzuela, P. L.; Rivas, F.; Sánchez-Martínez, G. (International Journal of Sports Physiology and Performance, 2021)
The COVID-19 pandemic has led many countries to implement strict lockdowns. This period of restricted movement might have negative consequences for all individuals, including loss of muscle mass and impaired physical performance and metabolic health.Elite athletes are also expected to suffer some level of detraining during this period of lockdown due to a reduction of training stimuli. However, the exact consequences of COVID-19 lockdown in elite athletes` performance and autonomic responses and the time required for athletes to recover their baseline status remain largely unknown.